Behavior and anxiety levels in pediatric patient: The behavioral changes and anxiety of pediatric patient in dental clinic - Rana A. Al Homoud; Amani K. Alshellatie; Abdullah S. Alzumaie; Sura A. Al‐Bayati (Wiley, 2023)
Abstract Aim The aim of this study is to evaluate the behavioral patterns and anxiety levels of pediatric patients in dental clinics, discern their behavioral expectations, and investigate the associations between these factors and the patient's age and gender. Methods In this cross‐sectional study, 150 pediatric patients visiting Sharjah Thumbay Dental Hospital for treatment were recruited over a study period of 23 weeks (February 12, 2022 to July 23, 2022). The patient's age ranged from 2 to 14 years. Guardians were informed about the study and their written consent was taken. Exclusion Criteria Children over 14 years old, children whose guardians refused to participate in the study, and medically compromised children. Frankl's behavior rating scale, Categorical rating scale, and Venham anxiety and behavioral rating scales were used to evaluate the pediatric patient's behavior and anxiety at the end of the dental visit, the evaluation was done by the same trained dental student for all the patients. Results When the Mann-Whitney U test was used for gender, no significant differences were observed in behavior and anxiety between male and female patients across all scales employed in this study. Conversely, when examining various age groups for behavior and anxiety using the Kruskal-Wallis test, significant findings emerged across nearly all scales. In the categorical rating scale, the age group of 11-14 years exhibited the most notable results in subscales of crying (p = .034), cooperativeness (p = .002), and apprehensiveness (p = .003). Conclusion The pediatric patients who took part in this study exhibited heightened anxiety when attending dental clinics. This study underscores the importance of understanding child behavior and utilizing effective communication with children and their guardians. Dental professionals should consider implementing strategies to manage child behavior during visits. Further research is required to develop sufficient strategies tailored to different pediatric populations, aiming to enhance dental care outcomes for pediatric patients.